Маніпулювання історичними фактами як елемент виправдання воєнної агресії росії проти України - Сарапій, Мар’яна Миколаївна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The study describes the manipulation potential of twisting historical facts as an element of justifying Russia’s aggression against Ukraine. To illustrate, the speech of president-dictator Putin on February 24, 2022, where he announces the beginning of a full-scale war against Ukraine, is taken. The study reveals the dominant distorted facts of the period of the Russian-Ukrainian war, which can also function in the domestic information space, but first of all they are a tool of the Russian information war aimed at the residents of the Russian Federation in order to justify the attack on Ukraine.